How is the brain working? Research on brain oscillations and connectivities in a new "Take-Off" state - Düzgün, Aysel; BAŞAR, EROL (My University, 2016)
The present report is a trial to survey analysis and applications of brain oscillations in cognitive impairment for opening the way to a new take off in research on brain oscillation. Although the number of papers related to brain oscillations rapidly increases, it is important to indicate the common principles governing the functioning of brain oscillations in the brain and body. Research scientists need a global view on the types of analysis, applications and existing oscillations. Further, scientists dealing with brain oscillations must have some knowledge from theoretical physics, system theory, and also general philosophy. The neuroscientists working on brain oscillations can mentally integrate several papers in the present report, and try to discover new avenues to augment knowledge on brain functions. A new take off in the search of brain oscillations indicates the strong need to survey this brunch of neuroscience in a broad panoply of science. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: EEG; Brain Oscillations; Delta-Oscillations; Ambiguous Motion Pattern; Alzheimer's; Schizophrenia; Connectome; Brain-Body; Memory